THE USE OF SONG ON SPOTIFY APP TO IMPROVE STUDENTS' LISTENING ABILITY - Qurrota A'yun, Khoirin Nida; Reti Wahyuni, M.Pd. (Media Antartika Indonesia, 2024)
Listening skills are a crucial component of English language learning, encompassing the understanding of intonation, pronunciation, vocabulary, and grammar. Listening is a fundamental part of daily communication and one of the most essential language skills. This study explores enhancing students' listening skills using English songs available on the Spotify application. Listening to songs transcends mere entertainment; it offers an engaging and effective medium for learning English. By utilizing Spotify's extensive library of songs and its integrated lyrics feature, students can improve their listening skills in an enjoyable and accessible manner. Furthermore, this method helps students better comprehend native English speakers, fostering linguistic proficiency and cultural familiarity. Employing brainstorming and interviews as research methodologies, this qualitative research highlights the benefits and challenges of integrating Spotify into the learning process. Results indicate that songs increase student motivation and improve listening comprehension, making Spotify a valuable tool for language acquisition.